Health-Related Quality of Life in Elderly Patients with Pacemakers - Natielly Aleixo Inácio; Manoel Muniz Neto; Antônio da Silva Menezes Junior; Joaquim Ferreira Fernandes; Vinícius Araújo Barbosa; Tiago de Almeida Laranjeira; Marcos Arruda (Brazilian Journal of Cardiovascular Surgery, 2021)
Abstract Introduction: Cardiac pacemaker (PM) therapy is of paramount importance. PM use increases with age, with an estimated increased use of 70% to 80% in patients over 65 years. This study evaluated the perception of the health-related quality of life (HRQoL) of elderly patients with PM, comparing them with patients without PM, by applying two quality of life questionnaires: EuroQoL 5-dimensions (EQ-5D) and 36-Item Short Form Health Survey (SF-36). Methods: This study included elderly patients divided into a group with PM and another without PM. Information on HRQoL was obtained using the EQ-5D and SF-36 questionnaires. Results: The study involved 104 elderly patients with PM and 150 without PM. The distribution of responses to the EQ-5D was similar between groups. Statistical differences within the gender variable in the group of elderly people with PM were significant for the mobility, habitual activities, and anxiety/depression domains and for the average EQoL utility score and visual analogue scale (EQ-VAS). Elderly patients with PM presented significant differences between New York Heart Association classes 1 and 2 for the mobility domain and EQ-VAS, while those evaluated through SF-36 presented higher averages in vitality, general health status, and pain. However, a different analysis was observed in the physical aspect domain. Conclusion: The SF-36 demonstrated that elderly patients with PM had an HRQoL similar to or greater than those without PM. However, the results of the EQ-5D did not show significant differences regarding the implantation of PM and HRQoL between the two groups of elderly individuals in the study.